2019
DOI: 10.1016/j.jbiomech.2018.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of functional deficits at the single muscle fiber level in experimentally-induced renal insufficiency

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…These findings suggest that the underlying molecular contractile mechanisms, such as myofilament properties and myosin/actin interactions, are likely altered in CKD. In support of this hypothesis, single-fiber force production per muscle size was reduced in an animal model of CKD; however, only one myosin heavy chain (MHC) isoform, MHC IIX, was examined in this study (4), and the other functionally important isoforms, MHC I, IIA, and IIB, may respond differently to CKD. Understanding the molecular mechanisms behind the reduced skeletal muscle function in CKD is an important step in developing interventions to maintain physical function in patients.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…These findings suggest that the underlying molecular contractile mechanisms, such as myofilament properties and myosin/actin interactions, are likely altered in CKD. In support of this hypothesis, single-fiber force production per muscle size was reduced in an animal model of CKD; however, only one myosin heavy chain (MHC) isoform, MHC IIX, was examined in this study (4), and the other functionally important isoforms, MHC I, IIA, and IIB, may respond differently to CKD. Understanding the molecular mechanisms behind the reduced skeletal muscle function in CKD is an important step in developing interventions to maintain physical function in patients.…”
Section: Introductionmentioning
confidence: 89%
“…Elevated P i and H + reduce the force and power generation of skeletal muscle fibers (11), in part from their large effect on the myosin-actin cross-bridge cycle (12). CKD may alter the sensitivity of skeletal muscle proteins to metabolic byproducts because reducing pH alone causes a larger decrease in single-fiber specific tension in an animal model with CKD (4). However, no prior studies have addressed muscle fatigue in CKD by altering both P i and H + in single fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also reported additional muscle abnormalities at the muscle biopsy level including oxidative/nitrosative stress (14,15), inflammation (16,17), fat accumulation/infiltration (16,17) and fibrosis (18,19) which may also affect muscle contraction. Moreover, a previous study from our group (20) in an animal model of CKD, reported that muscle dysfunction of single muscle fibers, is not fully explained by atrophy (11% smaller fiber areas compared to control fibers). Specifically, a significantly lower maximal isometric force was observed in CKD muscle fibers compared to controls even after correcting the values for the observed atrophy.…”
Section: Introductionmentioning
confidence: 84%
“…Determining the individual impact of each of these components using whole body and whole muscle function can be difficult, so a reductionist approach may be needed to determine the specific mechanisms behind the loss of physical capacity. One means of examining myopathy independent of neuropathy and other confounders is to examine single fiber contractile function as these measurements are performed on fibers without an excitable membrane, due to being chemically skinned, and within their normal three‐dimensional structure, protein content, and ionic conditions (Höök et al, 2001 ; Miller et al, 2013 ; Miller et al, 2015 ; Mitrou et al, 2019 ; Momb et al, 2022 ; Toth et al, 2013 ). Single fiber force production (cellular level) and the underlying myofilament mechanical properties (molecular level), including myosin‐actin cross‐bridge kinetics, can be assessed within the same fiber (Kawai & Halvorson, 1991 ; Miller et al, 2010 ; Momb et al, 2022 ; Zhao & Kawai, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…These prior studies using animal models (Mitrou et al, 2019 ; Momb et al, 2022 ) have provided initial insights into the underlying contractile deficits of advanced CKD in adults as, to our knowledge, no human studies have reported these measures. Furthermore, no human or animal studies have examined the impacts of early‐stage CKD on cellular and molecular contractile function.…”
Section: Introductionmentioning
confidence: 99%